EFFECTIVE EDUCATIONAL VIDEO: TYPES, DIDACTIC FUNCTIONS, CRITERIA (EDUCATION IN THE 21ST CENTURY, 2023)
The article identifies the key elements of the effective didactic use of video in theeducational process and the attempts to answer the following questions are made: whatkind of video can achieve the greatest didactic effect? What should be changed today indidactic approaches and methods? What are the positive aspects and disadvantages ofusing video in the educational process? To understand how to implement video in thelearning process competently from a didactic point of view, it is necessary to study thetypes of educational videos, the concept of their use and the criteria for effective teachingvideos.The author of this article being a member of the PRINTeL project took a ToT courseon “Video as a Learning Tool for Teachers and Students//Video Lecturing and PromotingInteraction in the Classroom” at the University of Porto (Portugal) in November 2018.The methodological basis of this study were the works of Z. Woolfitt, A.W. Bates, J.Day, C. Clark & R. Mayer, A. Deal, L. Germany, P. Gorissen, J. Koumi.The purpose of the research carried out within the framework of this article is to analyzethe existing types of educational videos, the concepts of their use and the criteria foreffective teaching videos. The use of new tools or approaches to learning should be basedon a holistic view of the needs of all students, the subject area and learning objectives,and not on the false idea of what this modern generation of students’ demands from us. Ifwe want to use all the advantages of video lectures and introduce this technology into oureducational process effectively, then teachers need appropriate and adequate support forthis in the form of staff advanced training.
Keywords: Digital literacy, video lecture, efficiency, blended learning, flipped class